![image](https://tex.z-dn.net/?f=%5Cleft+%5C%7B+%7B%7Bx%2By%3D15%7D+%5Catop+%7Bx%2Ay%3D-54%7D%7D+%5Cright.+%5C%5C+%5C%5C+x%3D15-y+%5C%5C+%5C%5C+%2815-y%29%2Ay-54%3D0+%5C%5C+%5C%5C+y%5E2-15y%2B54%3D0+%5C%5C+%5C%5C+D%3Db%5E2-4ac%3D15%5E2-4%2A1%2A54%3D9%3E0+%5C%5C+%5C%5C+y_1%3D+%5Cfrac%7B-b-+%5Csqrt%7BD%7D+%7D%7B2a%7D+%3D+%5Cfrac%7B15-+%5Csqrt%7B9%7D+%7D%7B2%2A1%7D+%3D+%5Cfrac%7B12%7D%7B2%7D+%3D6+%5C%5C+%5C%5C+y_2%3D+%5Cfrac%7B-b%2B+%5Csqrt%7BD%7D+%7D%7B2a%7D+%3D+%5Cfrac%7B15%2B+%5Csqrt%7B9%7D+%7D%7B2%2A1%7D+%3D+%5Cfrac%7B18%7D%7B2%7D+%3D+9+%5C%5C++%5C%5C+x_1+%3D+15-6%3D9+%5C%5C++%5C%5C+x_2+%3D+15+-+9%3D6%0A)
0 \\ \\ y_1= \frac{-b- \sqrt{D} }{2a} = \frac{15- \sqrt{9} }{2*1} = \frac{12}{2} =6 \\ \\ y_2= \frac{-b+ \sqrt{D} }{2a} = \frac{15+ \sqrt{9} }{2*1} = \frac{18}{2} = 9 \\ \\ x_1 = 15-6=9 \\ \\ x_2 = 15 - 9=6
" alt="\left \{ {{x+y=15} \atop {x*y=-54}} \right. \\ \\ x=15-y \\ \\ (15-y)*y-54=0 \\ \\ y^2-15y+54=0 \\ \\ D=b^2-4ac=15^2-4*1*54=9>0 \\ \\ y_1= \frac{-b- \sqrt{D} }{2a} = \frac{15- \sqrt{9} }{2*1} = \frac{12}{2} =6 \\ \\ y_2= \frac{-b+ \sqrt{D} }{2a} = \frac{15+ \sqrt{9} }{2*1} = \frac{18}{2} = 9 \\ \\ x_1 = 15-6=9 \\ \\ x_2 = 15 - 9=6
" align="absmiddle" class="latex-formula">
или по теореме Виета y₁ + y₂ = 15 y₁ * y₂ = 54
y₁ = 6
y₂ = 9
x₁ = 15 - 6 = 9
x₂ = 15 - 9 = 6
Ответ:
D. 6; 9